Patient safety and health care management - Savage, Grant T. 1954-; Ford, Eric W. (Emerald, 2008)
This volume on patient safety revolves around a central question: How can the increased emphasis on patient safety among healthcare managers be translated into better policy and reduced clinical risk? The twelve contributions in this volume are divided between four sections: theoretical perspectives on managing patient safety; top management perspectives on patient safety; health information technology perspectives on patient safety; and organizational behavior and change perspectives on patient safety. The issue of patient safety provides a fertile niche for management researchers to test existing theories and develop new ones.For example, the goal of reducing medical errors while maximizing patient health requires not only an awareness of the tenets of evidence-based medicine, but also the managerial theories of human relations, organizational culture, organizational development, organizational learning, organizational structure, quality improvement, and systems thinking. Indeed, these and other managerial theories are drawn upon and applied by the various contributors. Taken together, the thirty-five authors of this volume demonstrate that the future of patient safety requires healthcare professionals and managers who can successfully engage in multi-faceted projects that are socially and technically complex.
Keywords: Health services administration.; elektronické knihy; electronic books